PEMBERDAYAAN MASYARAKAT MELALUI GERAKAN CEGAH STUNTING DI KAMPUNG KELUARGA BERKUALITAS (GUNTING KERTAS) - Rafi Muhammad Fauzi; Lilis Karwati; Nastiti Novitasari; Dimas Sunarya; Mega Silpia Agustin; Gigin Ginayaturrohmah; Dzuliani Faseha (Jurnal Pengabdian Masyarakat Indonesia, 2023)
Empowerment, the community in the process of preventing stunting which targets pregnant women, breastfeeding mothers, mothers of toddlers, toddlers and teenagers who are located in Kembang Mulya KB Village in Padamulya Hamlet, Padamulya Village, Cihaurbeuti District, this program is designed in the form of outreach as an effort to prevent stunting is now in focus the main government to achieve the goal of West Java Zero Stunting in 2024 and to prepare for the demographic bonus that is expected to occur in Indonesia in 2030. Based on these problems, it is important that it is implemented through a stunting prevention program by the public education department as a Community Empowerment Facilitator through Family Planning Program Extension, and Community Health, Social, Village Facilitator Staff , as a Development Facilitator, namely becoming an Education, who has social mapping skills and provides an objective view of situation analysis, potential and social problems in society.